Design of a low-power, high performance, 8×8bit multiplier using a Shannon-based adder cell - SENTHILPARI, C; SINGH, A; DIWAKAR, K (ELSEVIER SCI LTD, 2008)
In this paper, we have developed a new full-adder cell using multiplexing control input techniques (MCIT) for the sum operation and the Shannon-based technique to implement the carry. The proposed adder cell is applied to the design of several 8-bit array multipliers, namely a Braun array multiplier, a CSA multiplier, and Baugh-Wooley multipliers. The multiplier circuits are designed using DSCH2 VLSI CAD tools and their layouts are generated by Microwind 3 VLSI CAD tools. The output parameters such as propagation delay, total chip area, and power dissipation are calculated from the simulated results. We have also calculated energy per instruction (EPI), throughput, latency, signal-to-noise ratio (SNR), and the effect of temperature on the drain current by using the generated layout output parameter of a BSIM 4 advanced analyzer. The simulated results of the proposed adder-based multiplier circuit are compared with a cell multiplier that utilizes a MCIT-based adder, a cell multiplier composed of complementary pass transistor logic-based (CPL) adders and those of other published multipliers circuits. From the analysis of these simulated results, it was found that the proposed multiplier circuit gives better performance in terms of power, propagation delay, latency and throughput than other published results. (C) 2007 Elsevier Ltd. All rights reserved.